2016
DOI: 10.1016/j.stemcr.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

No Identical “Mesenchymal Stem Cells” at Different Times and Sites: Human Committed Progenitors of Distinct Origin and Differentiation Potential Are Incorporated as Adventitial Cells in Microvessels

Abstract: SummaryA widely shared view reads that mesenchymal stem/stromal cells (“MSCs”) are ubiquitous in human connective tissues, can be defined by a common in vitro phenotype, share a skeletogenic potential as assessed by in vitro differentiation assays, and coincide with ubiquitous pericytes. Using stringent in vivo differentiation assays and transcriptome analysis, we show that human cell populations from different anatomical sources, regarded as “MSCs” based on these criteria and assumptions, actually differ wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
375
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 372 publications
(404 citation statements)
references
References 42 publications
15
375
1
1
Order By: Relevance
“…In vitro, CB-BFs display osteogenic and chondrogenic differentiation potential , whereas they have a reduced or virtually absent capacity to generate adipocyte-like cells (Kern et al, 2006;Goodwin et al, 2001;Zhang et al, 2011;Bieback et al, 2008;Karagianni et al, 2013). When transplanted in vivo with osteoconductive ceramic scaffolds, CB-BFs are able to form histology-proven bone (Zhang et al, 2011;Liedtke et al, 2016;Sacchetti et al, 2016). Interestingly, we have also demonstrated that CB-BFs consistently form cartilage in open heterotopic transplants, a property that is usually not observed in BMSCs.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…In vitro, CB-BFs display osteogenic and chondrogenic differentiation potential , whereas they have a reduced or virtually absent capacity to generate adipocyte-like cells (Kern et al, 2006;Goodwin et al, 2001;Zhang et al, 2011;Bieback et al, 2008;Karagianni et al, 2013). When transplanted in vivo with osteoconductive ceramic scaffolds, CB-BFs are able to form histology-proven bone (Zhang et al, 2011;Liedtke et al, 2016;Sacchetti et al, 2016). Interestingly, we have also demonstrated that CB-BFs consistently form cartilage in open heterotopic transplants, a property that is usually not observed in BMSCs.…”
Section: Introductionsupporting
confidence: 53%
“…The cartilaginous tissue was formed in the absence of any ex vivo induction, thus demonstrating the inherent capacity of CB-BFs to undergo chondrogenesis even in the absence of specific inducing agents . However, in none of the previous studies was CB-BF differentiation associated with the establishment of a hematopoietic microenvironment (Zhang et al, 2011;Sacchetti et al, 2016). The results presented here provide further elucidation of the biology of CB-BFs, demonstrating that CBBFs were able to generate complete pellet-derived ossicles in vivo in which a functional HSC niche was created.…”
Section: Discussionmentioning
confidence: 63%
“…Mesenchymal "stem" cells (MSCs) have been isolated from virtually all tissues and organs, however, the lack of specific markers has made their characterisation challenging, particularly in light of a recent report showing that mesenchymal stromal cells from different tissues have different transcriptome profiles and differentiation potentials (Sacchetti et al, 2016). Given the advanced state of analysis interstitial cells in muscle, it would be important to establish their lineage relationships and myogenic potential, and define more clearly general features of MSCs.…”
Section: Cellular Regulators Of Muscle Repair and Their Regenerativementioning
confidence: 99%
“…BM-MSCs are endowed with the ability to differentiate in four canonical lineages, osteoblasts, chondroblasts, adipoblasts and reticular stromal cells supporting HSCs, underlying their regenerative activity. MSCs were first discovered in BM, (other) tissue-specific MSCs have been recently recognized and studied [30,27,24,2]. In this manuscript, we utilize primary peri-cryptic colonic SMA + MSCs endowed with all BM MSCs functions but adipogenesis [30] to explore the role of miR-204&211 in their differentiation.…”
Section: Discussionmentioning
confidence: 99%